2019
DOI: 10.1021/acs.inorgchem.9b00975
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Driven Chelation and Kinetic Separation of Select Rare Earths Using a Tripodal Nitroxide Proligand

Abstract: Separation of the rare-earth (RE) elements (Sc, Y, La–Lu) is challenging because of their similar chemical properties, but is necessary for their applications in renewable energy and electronic device technologies. The development of separation processes driven by kinetic factors represents a new area for this field. Herein, we disclose a novel method of separating select rare earths by reacting RE cyclopentadienides with the triradical species tris­(2-tert-butylnitroxyl)­benzyl­amine (1). The key proligand 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Several alternative separations techniques have been demonstrated in recent studies including processes based upon selective crystallization and precipitation, photochemical reduction, , or chemical kinetics, , rather than liquid–liquid extraction. , Chromatographic separations using functionalized materials and bioinspired separations processes that rely upon bioadsorption , or mineralization techniques have also been reported recently. There is general interest in the development of a system in which modification of the local coordination sphere of the RE cations leads to the optimization of separation efficiencies for a targeted RE mixture.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several alternative separations techniques have been demonstrated in recent studies including processes based upon selective crystallization and precipitation, photochemical reduction, , or chemical kinetics, , rather than liquid–liquid extraction. , Chromatographic separations using functionalized materials and bioinspired separations processes that rely upon bioadsorption , or mineralization techniques have also been reported recently. There is general interest in the development of a system in which modification of the local coordination sphere of the RE cations leads to the optimization of separation efficiencies for a targeted RE mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the RE­(TriNOx) separation system, in which binary LRE/HRE mixtures were separated with a single leaching step in benzene or toluene solutions, was caused by differences in solubilities of monomeric/dimeric species formed in situ . , It was determined that LRE complexes more-readily formed a benzene or toluene-soluble dimeric species, [RE­(TriNOx)] 2 , while the smaller, HRE cations did not self-associate in these solutions and remained largely insoluble in aromatic organic solvents. It was demonstrated that the performance of the RE­(TriNOx) separation system could be influenced by using the redox properties of the ligand , or by changing the apical ligand (Figure ). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that context, functional groups such as (thio)urea, amide, pyrrole, or imidazole have attracted considerable attention due to their donor/acceptor properties and geometrical features. 15,[22][23] Given our interest in hydroxylamine ligands (R 1 R 2 NOH), [25][26][27][28][29][30][31] and recognizing their potential for anion binding by means of vicinal H-bond acceptors associated with mildly acidic protons, we initiated studies on the propensity of a tripodal receptor (H3TriNOx) for anion capture (Scheme 1). As hydroxylamine moities have not been examined in this context previously, it was of interest to interrogate their interactions with halides under a range of conditions, including condensed and gas phases, to determine fundamental thermodynamic trends.…”
Section: Introductionmentioning
confidence: 99%